Development of Innovative Taro-Based Product Management with Zero-Waste Concept to Increase the Independence of PKK Wanagiri - Suriati, Luh; Selamet, I Ketut; Sukmadewi, Desak Ketut Tristiana (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
The development of innovative products is currently growing rapidly producing a variety of processed products that are increasingly diverse. Taro tubers are one of the potential foodstuffs to be developed. Taro in addition to having carbohydrate component, also contains other components that are good for health. Taro has the disadvantage of itching when consuming taro due to the oxalate compounds contained in it. This has resulted in people being reluctant to process taro. This problem was experienced by one of the groups in Wanagiri Village, namely the Prosperous Family Empowerment Group (PKK) Wanagiri, which is located in Sukasada District, Buleleng Regency, Province Bali, Indonesia. The partner does not yet know the taste of taro, and does not have innovative product management made from taro. Solutions to overcome such problems are: providing knowledge regarding the cultivation and processing of taro, providing training on the processing of taro products (bread, nuggets and jams) and how to package, market and handle processing waste. The method used is active community participation. Community Self-Reliance Activities (KKM) in Wanagiri Village have been running smoothly. The added value of the Wanagiri PKK group and their standard of living has increased. Taro-based innovative product development with a zero-waste concept can be applied. Knowledge of how to process taro into bread, nuggets, chips and jam, product packaging, and marketing can help people to increase self-sufficiency. Mentoring activities should be carried out on an ongoing basis so that groups are able to independently make products (chips, bread, nuggets and jam), wider marketing and ultimately increased welfare.